CYTOTOXIC ACTIVITY OF SELECTED NIGERIAN PLANTS - Sowemimo, Abimbola A; van de Venter, Maryna; Baatjies, Lucinda; Koekemoer, Trevor (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cancer is one of the most prominent human diseases which has stimulated scientific and commercial interest in the discovery of new anticancer agents from natural sources. The current study investigates the cytotoxic activity of ethanolic extracts of sixteen Nigerian plants used locally for the treatment of cancer using the MTT assay on the HeLa cell line. Sapium ellipticum leaves showed activity comparable to the reference compound Cisplatin and greater cytotoxic activity than Combretum paniculatum, Celosia trigyna, Drymaria cordata, Cyathula achyranthoides and Cyathula prostata. Justica extensa, Pupalia lappacea, Hedranthera barteri leaves, Alternanthera sessilis, Ethulia conyzoides leaves, Combretum zenkeri root, Sapium ellipticum stembark and Lannea nigritana stembark showed very low activity while Combretum molle, Adenanthera parvoniana and Lannea acida showed no activity. The results justify the use of Sapium, Combretum, Celosia, Drymaria and Cyathula in traditional treatment of cancer.